1995
DOI: 10.1017/s0022215100130968
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillar lipoma: a case report

Abstract: Benign tumours of the tonsils are rare. Only a few cases of tonsillar lipoma have been previously reported. The case of a pedunculated polypoid lipoma of the palatine tonsil in a 44-year-old Japanese woman is presented. The ‘polyp’ was excised and an histopathological examination was carried out. The ‘polyp’ contained dilated lymphatics in the dense fibrous connective tissue beneath the overlying mucosal epithelium and below the mature fat tissue with intervening strands of fibrous tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Tonsillectomy with the excision of the lesion has been described as the most common treatment option for tonsillar lipomas, while surgical excision of the lipoma and stalk, without tonsillectomy, has rarely been described in the literature [9, 12]. The present case was managed with excision of the stalk without the need of tonsillectomy.…”
Section: Discussionmentioning
confidence: 85%
“…Tonsillectomy with the excision of the lesion has been described as the most common treatment option for tonsillar lipomas, while surgical excision of the lipoma and stalk, without tonsillectomy, has rarely been described in the literature [9, 12]. The present case was managed with excision of the stalk without the need of tonsillectomy.…”
Section: Discussionmentioning
confidence: 85%
“…[3,8] Dereköy et al [9] defined a case of tonsil lipoma that was 3.6 centimeters in length and caused dyspnea, hypoxemia and respiratory acidosis. Furthermore, Harada et al [14] reported a 44-year-old Japanese woman with an asymptomatic polypoid palatine tonsil lipoma 1.6x1.5x1.3 centimeters length. Apart from these, our patient had difficulty in swallowing, a sensation of nausea and a feeling of respiratory obstruction while sleeping at night.…”
Section: Discussionmentioning
confidence: 99%
“…Our search of the English language medical literature yielded only nine documented cases of tonsillar lipoma and one case of peritonsillar lipoma (Table 1). [1][2][3][4][5][6][7][8][9] There was no reported gender predominance, and the average age of the patients was 56.7 years (range, 17-83 years). Lipomas of the tonsil were described as occasionally being accompanied by soreness, cough, snoring, excessive salivation, chronic tonsillitis, respiratory difficulties or, as in our case, as a foreign body sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of a tonsillar lipoma is surgical excision. We performed an elective excision of the mass under local anesthesia, as did Harada 7 and Bégin and Frenkiel. 9 Others elected to excise it by performing a unilateral tonsillectomy with the patient under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%